Development of Capture Fisheries in The Bajomulyo Coast Fishery Port, Juwana District, Pati District, 2010-2015 - Fitriani, Danik; Alamsyah, Alamsyah (Journal of Maritime Studies and National Integration, 2024)
This study discusses the development of capture fisheries at the Bajomulyo Coastal Fishing Port (PPP), Juwana District, Pati Regency, 2010-2015. The sources used in this research are documents from the Ministry of Maritime Affairs and Fisheries and related agencies as well as research related to Juwana Port. This study found that the development of capture fisheries at Juwana Port experienced ups and downs in terms of fish income, which was influenced by the number of vessels, fish sales methods, and the use of fishing gear. The construction and development of the PPP Bajomulyo also contributes to the development of capture fisheries products. The presence of freezer vessels in PPP Bajomulyo continues to increase, thereby increasing the quality and price of fish. The ship owners added a new ship specifically for freezer ships. The decrease in fish production was due to the direct sales of fish to buyers, changes in auction mechanisms, a decrease in the number of ship departures, and overfishing.